Prevalence and some associated factors of overweight in year 8 students of girls only schools in the Gampaha Municipal Council in 2005. - Sudasinghe, S.P.B.H (My University, 2006)
A cross-sectional descriptive study to determine the prevalence and some associated factors of overweight. The total study population was 698. Non-response rate was 5.8 percent. Students' weight was measured using an electronic solar power weighing scale to the closest 100g. Their height was measured using a microtoise tape to the nearest 0.1 cm. Information regarding the socio-demographic and economic factors, food consumption pattern, activity pattern, birth weight, breast feeding duration, parental body size, knowledge on nutrition were obtained by two questionnaires filled by the student and the parent or guardian. Obesity and overweight were defined using gender and age specific body mass index (BMI) criteria recommended by the International Obesity Task Force. (IOTF).The prevalence of overweight was 7.73 percent and that of obesity was 2.05 percent. Knowledge on nutrition was not satisfactory in the study population. Sitting time more than eight hours.